Exploration of The Traditional Game of Galah Hadang: Does it Effect The Concentration, Agility and Endurance of Early Age Badminton Players? - Manihuruk, FransFile; Sumaryanto, Sumaryanto; Nugroho, Sigit; Nasrulloh, Ahmad; Sumarjo, Sumarjo; Sumaryanti, Sumaryanti (Journal of Sport Science and Education, 2023)
This study aims to determine the effect of traditional galah hadang games on concentration, agility and endurance in early athletes aged 8-11 years. This study used an experimental method with a design of one group pre-test post-test. The population in this study was 20 badminton athletes at an early age PB (Badminton Union).PT. One asahan. The sample in this study was 20 badminton athletes PB (Badminton Union).PT. One Asahan with sampling using total sampling. The analytical technique used is quantitative descriptive which is analyzed by the Paired T Test. The results showed a sig value of p= 0.00 (< 0.05) so that it was concluded: There is an influence of the traditional game of galah hadang on increasing the concentration of early age badminton athletes, there is an influence of the traditional game of galah hadang on increasing the agility of early age badminton athletes, andthere is an influence of the traditional game of galah hadang on increasing the endurance of early age badminton athletes. With the results of this study, it is expected that there will be a new study that develops a traditional game training model of galah hadang applied to early age badminton athletes.